Ab-initio and Statistical Calculations to predict the Rate Constant of Several Ethers Reactions with Chloramine-T - Ahmed Sadoon; Ayman Mohamed Taib (College of Education for Pure Sciences, 2021)
Abstract. The prediction of rate constant of Ethers reaction with Chloramine-T has been studied theoretically in this work using ab-initio and statistical calculations. The first order reaction between Ethers and Chloramine-T shows that the rate constant depends on the Ethers concentration. Therefore, ab initio calculations were used using DFT/ b3lyp with 6-311++G** as a basis set to extract the most stable geometry of the chosen ethers. Also, several physical parameters have been gained form these calculations such as mulliken charge at the active atoms, dipole moment, Homo and Lomo energy levels, Hardness, Electronic Chemical Potential and Global Electrophilicity Index. The relationship between these physical variables plays an effective role in the reaction rate. Therefore, statistical calculations were used to investigate the possible relationship between these physical parameters. These relationships can be predicted from the value of the correlation coefficient (R2) and the Standard error (SE). Simple regression analysis and multiple regression analysis were performed between these physical variables as independent variables and rate constant as a dependent variable using SPSS software. The results show high value of R2 (0.993) of the regression analysis which reflects the high relationship between these variables that affects the reaction rate concentration. The out data illustrates negligible differences (about 0.008) between the experimental and calculated rate constant value.